An Armington-Leontief model - Ferrán Sancho (Journal of Economic Structures, 2019)
We develop a novel linear equilibrium model with an Armington flavor. We provide (1) proof of the solvability of the model and of the existence and non-negativity of the equilibrium solution and of the newly derived multiplier matrix; we also show (2) that the standard Leontief multiplier matrix arises as a special case of this new model and (3) that this model allows the computation of multiplier effects with no external output bias, which is particularly relevant for applied economic analysis.
Keywords: C62; C67; D57; 330; Armington principle; Extended linear equilibrium model; Solvability; Technological productivity